Implementasi Reward dan Punishment dalam Disiplin Waktu ASN pada Badan Kepegawaian Daerah Provinsi Kalimantan Tengah - Ayunda Fitria Ramadhani; Julianes Rani Agustina (Pusat Riset dan Inovasi Nasional, 2026)
The implementation of a reward and punishment system is considered capable of improving employee work discipline. Rewards are given to encourage employee morale, while punishments are given as a reminder of the consequences of misconduct. This study aims to describe the implementation of the reward and punishment system in the Civil Service. Through a qualitative approach with in-depth observation, structured interviews with employees, and documentation studies. The results of the study found that the implementation of the reward and punishment system has been carried out well, with rewards given based on the level of discipline and performance of employees, while punishments are given based on the type of violation committed. The rewards given include Additional Employee Income, the Satyalancana Karya Satya award, exemplary employee awards, internship certificates, and retirement awards. Meanwhile, the punishments given include verbal warnings, written warnings, deductions from Additional Employee Income, and severe sanctions for employees with serious violations.